Review Digital Marketing And Hedonic Shopping Value Affect Impulsive Buying : Review Digital Marketing And Hedonic Shopping Value Affect Impulsive Buying - Nining, Andria Ningsih; Hurnis, Delfi; Triani, Mike (Asean International Journal of Business, 2022)
Purpose – This study empirically examines the effect of digital marketing on impulse buying with the experience of hedonic shopping values ​​and the income results of SME actors as mediators. Methodology/approach – This study uses Partial Least Square (PLS) to analyze the data. Data were collected from customers who often shop at food and clothing SMEs as the population of this study. The sample is 200 visitors in Bukittinggi City, the result of non-probability sampling using purposive sampling technique. Findings – The findings show that digital marketing affects impulse buying directly and does not directly affect the value of hedonic shopping and income as a mediator. Novelty/value – This study shows a greater awareness of the importance of using digital marketing as a means of selling for business actors so that they can further increase the motivation of consumers' hedonic shopping values ​​which are still low, so that they can affect income results and also trigger consumers to make impulse purchases. Keywords: Digital Marketing, Hedonic Shopping Value, Income, Impulsive Purchase.